Electron removal from H2O by hydrogen-like projectile impact. (April 2022) - Jana, D.; Purkait, K.; Samaddar, S.; Haque, A.; Purkait, M.
Abstract: The four-body distorted-wave approximation (DW-4B) is used to investigate the electron removal from water molecules by the impact of hydrogen-like projectiles. The incident energy is considered in a range of 20 to 2000 keV/amu. Our goal is to establish the relative importance of the intermediate ionization continua of the active electron and the electron–electron correlations. The calculations are based on the independent electron model. The description of initial ground state molecular orbitals of water are described by a complete-neglect-of-differential-overlap method based on the linear combination of atomic orbitals. Numerical results for the total cross sections are compared with other results and found to be in good agreement with the available experimental findings. Differentiation between the reactions of single-electron ionization and single-electron capture in electron removal process as a function of impact energies is also analyzed. Finally, the dependence of cross sections regarding electron removal on different descriptions of molecular orbitals as well as the simplest additivity rule are discussed. Highlights: Four body distorted-wave model is used to study the electron removal process. Theoretical cross sections data about the ionization and capture are needed in fundamental studies of charged particle interaction in biological matter. Dressed projectile effects the cross sections of electron ionization and electron capture. Graphical abstract: